Donovan's reef [videorecording (DVD)] - Ford, John, 1894-1973; Nugent, Frank S.; Grant, James Edward, 1905-1966; Wayne, John, 1907-1979; Marvin, Lee; Allen, Elizabeth, 1929-2006; Warden, Jack; Romero, Cesar, 1907-1994; Foran, Dick, 1910-1979; Lamour, Dorothy, 1914-1996; Clothier, William; Lovering, Otto; et al. (John Wayne collection., 2005)
A straight-laced Bostonian comes searching for her father, a brawling ex-Navy man living on a South Pacific island.